Proposed remedial programmed instruction on the English present tense - Sarmenta, Amelita (Gonzales) 1923- ([Quezon City publisher not identified], 1964)
The author proposed a material for remedial programmed instruction on the English present tense. The material allows each student to proceed at his own pace, in small steps, responding to every step and knowing immediately if he is right or wrong. The program may take the place of a tutor as it is carefully ordered and properly sequenced.
Thesis (Master of Arts in Teaching)--University of the Philippines
Keywords: English language -- Verb